PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS ASURANSI AKIBAT KONTRAK BAKU ASURANSI BERTENTANGAN DENGAN HUKUM - YENNY, YENNY (JURNAL CIVIL LAW USU, 2013)
Abstraksi : Standard contract is an agreement established unilaterally by the manufacturer and are commonly used. Inclusion of the exoneration clause in the standard contract outside the provisions resulting nullification of a contract. Policyholders who have paid premiums well-meaning would be hurt, so it is important to protect consumers. To examine the extent to which the agreement should contradict the lawsuit in court. The sanctions that may be imposed include: administrative sanction compensation determination; civil penalties in the form of demands for compensation; criminal sanctions in the form of a fine. Settlement of disputes outside the courts can be reached via BPSK to reach agreement on the shape and contour of compensation and / or on certain actions to ensure it will not happen again.   Keywords: Protection Law, Policy Holders, Insurance.